The paper wasps (Hymenoptera: Vespidae: Polistinae) of Sri Lanka recorded from recent investigations - Ranasinhe, Tharindu Dilshan; Abeywardhana, Lakmini; Nugaliyadde, Anupiya; Dangalle, Chandima Deepani (Zootaxa, 2024)
Paper wasps of subfamily Polistinae Lepeletier have been studied in many countries of the world due to their importance as pest species, predators, model organisms in research and medical significance. Seven species have been well documented in Sri Lanka, of these five species represent genus Ropalidia Guérin-Méneville, and two species genus Polistes Latrielle. However, the species have not been studied systematically for many years and recent records are not available. In the present study investigations for wasps (Vespidae) were conducted in 28 locations of all provinces and climatic zones of the country. Five species of paper wasps were found in 15 of the locations investigated, four in the genus Ropalidia and one in the genus Polistes. Ropalidia marginata Lepeletier was the most abundant and widely distributed species, while the other species had more limited distribution. Polistes (Gyrostoma) olivaceus De Geer, previously recorded from Sri Lanka, was not recorded during the present study. All the species of paper wasps encountered in the present study showed changes in distribution from their historical locations, decline in distributional ranges and occurrence in new locations.